WHAT IS BUSINESS? GARRY ALFONSIUS Bachelor of Science in Business Administration at Universal Institute of Professional Management UIPM Singapore - Garry Alfonsius (Universal Institute of Professional Management, 2021)
All of people know about business. A business is defined as an organization or enterprising entity engaged in commercial, industrial, or professional activities. Businesses can be for- profit entities or they can be non-profit organizations that operate to fulfill a charitable mission or further a social cause. The term